Absorption Performance of Doped TiO2-Based Perovskite Solar Cell using FDTD Simulation. (27th February 2022) - Mulyanti, Budi; Wulandari, Chandra; Hasanah, Lilik; Pawinanto, Roer Eka; Hamidah, Ida
Abstract : In the third generation of the solar cell era, significant trends in the development of perovskite solar cells (PSC) were observed. Exploring suitable materials for its wafer structure, such as perovskite and electron transport layers (ETL), were a major emphasis of high-performance PSC development. Because of its matching band structure to MaPbI3, TiO2 is the most often utilized material for ETL. However, in the application of TiO2 to PSC, electron trapping and a wide energy gap become a drawback. The goal of this research is to improve the absorption performance of PSC employing ETL with Fe and Ta-doped TiO2 as well as the thickness of the material. The interaction between the electromagnetic waves of light and the solar cell structure was calculated using Finite-Difference Time-Domain (FDTD) simulations, which resulted in the absorption spectra. In comparison to pure TiO2, which absorbs only 79.5% of the incident light, Fe-TiO2 and Ta-TiO2 as ETL in solar cells have increased absorption spectra to 81.7% and 81.2%, respectively. Finally, we may conclude that the optimum ETL layer parameters are 0.32% Fe doping and a thickness of 100 nm.